Do Be Malay(sian): 8TV’S Fantasy and the Malay Other - Luqman Lee (Kajian Malaysia, 2018)
In August 2011, Malaysian television station 8TV's three Ramadan public service announcements (PSA) garnered shocked responses from Malaysian Chinese viewers nationwide for their presumably ethno-condescending overtones. What may on the surface appear to be an issue of simple oversight by the broadcaster reveals upon closer examination to be indicative of two realities – the hierarchised interfaith and interethnic normative, and the increasing vocality of minority groups who seek to reconfigure this normativity. I posit that both realities are directly and tangentially productive of the very same racial-racist beliefs that were challenged. There are two facets to our inquiry – the purportedly "non-racist" intent of 8TV, and the racial lens through which the content was decoded. This paper discusses the paradox of Malaysian racial discourse through Žižek's transposition of Lacan's fantasy to the socio-political domain as ideological fantasy writ large on screen, where by alleging that 8TV's intent was racist, viewers were in fact identifying the gap between the symbolic discourse of Malay supremacy and its material realities. Moreover, by identifying with or alleging that 8TV's intent was racially-biased, it is argued that the viewers were necessarily racialist.